Reverse Address Resolution Protocol (RARP) - Sehrawat, Mr Rahul; Gupta, Mr Pankaj; Yadav, Mr Ravishu (IJRDO -Journal of Computer Science Engineering, 2015)
The Reverse Address Resolution Protocol (RARP) is an obsolete computer networking protocol used by a client computer to request its Internet Protocol (IPv4) address from a computer network, when all it has available is its Link Layer or hardware address, such as a MAC address. The client broadcasts the request, and does not need prior knowledge of the network topology or the identities of servers capable of fulfilling its request. RARP is described in Internet Engineering Task Force (IETF) publication RFC 903. It has been rendered obsolete by the Bootstrap Protocol (BOOTP) and the modern Dynamic Host Configuration Protocol (DHCP), which both support a much greater feature set than RARP. This research paper gives a brief introduction about Reverse Address Resolution Protocol (RARP) , Timing RARP Transactions ,Primary And Backup RARP Servers.